2005
DOI: 10.1002/jcc.20241
|View full text |Cite
|
Sign up to set email alerts
|

First‐principle studies of intermolecular and intramolecular catalysis of protonated cocaine

Abstract: We have performed a series of first-principles electronic structure calculations to examine the reaction pathways and the corresponding free energy barriers for the ester hydrolysis of protonated cocaine in its chair and boat conformations. The calculated free energy barriers for the benzoyl ester hydrolysis of protonated chair cocaine are close to the corresponding barriers calculated for the benzoyl ester hydrolysis of neutral cocaine. However, the free energy barrier calculated for the methyl ester hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 66 publications
4
54
0
1
Order By: Relevance
“…[10][11][12] Cocaine is highly lipophilic, so much so that treatment of cocaine overdose includes the administration of lipid emulsions to dampen its effects. 13 Cocaine is also hydrophilic; the hydrochloride salt is readily soluble in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Cocaine is highly lipophilic, so much so that treatment of cocaine overdose includes the administration of lipid emulsions to dampen its effects. 13 Cocaine is also hydrophilic; the hydrochloride salt is readily soluble in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]6 An alternative approach is to interfere with the delivery of cocaine to its receptors or accelerate its metabolism in the body. 4,[7][8][9][10][11][12][13][14][15][16][17] Butyrylcholinesterase (BChE), the principal plasma enzyme that catalyzes cocaine hydrolysis into its biologically inactive metabolites, is an ideal target for this purpose. There are some clear advantages of using this enzyme to accelerate the cocaine metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…First-principles electronic structure calculations accounting for solvent effects have been carried out to study the detailed competing reaction pathways of the non-enzymatic hydrolysis of cocaine and the corresponding free energy barriers. The first-principles computational studies 32,36 have confirmed the co-existence of the competing reaction pathways. Below, we will only discuss the hydrolysis of cocaine at the benzoyl ester group (Fig.…”
Section: Hydrolysis Of Chair Cocainementioning
confidence: 81%
“…1). Based on the first-principles reaction coordinate calculations, 32 the optimized transition state geometry is shown in Fig. 3 as TS1-boat.…”
Section: Hydrolysis Of Boat Cocainementioning
confidence: 99%
See 1 more Smart Citation